2020
DOI: 10.3390/jcm9041216
|View full text |Cite
|
Sign up to set email alerts
|

Common Musculoskeletal Disorders in the Elderly: The Star Triad

Abstract: Musculoskeletal disorders are debilitating conditions that significantly impair the state of health, especially in elderly subjects. A pathological triad of inter-related disorders that are highly prevalent in the elderly consists of the following main “components”: sarcopenia, tendinopathies, and arthritis. The aim of this review is to critically appraise the literature relative to the different disorders of this triad, in order to highlight the pathophysiological common denominator and propose strategies for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 116 publications
0
42
0
Order By: Relevance
“…The demand for total hip arthroplasty (THA) is quickly rising given the escalating global incidence of hip osteoarthritis [1,2] that is related both to the aging population and to the increases in obesity and sedentary behavior [2,3]. The efficacy of THA is well documented, and it is widely accepted that the post-surgery rehabilitation is key to optimize outcomes [4,5], in particular when the rehabilitation is based on intensive and early progressive exercises [6], which lead to improved clinical outcomes and patient satisfaction, and reduction of complications and expenses.…”
Section: Introductionmentioning
confidence: 99%
“…The demand for total hip arthroplasty (THA) is quickly rising given the escalating global incidence of hip osteoarthritis [1,2] that is related both to the aging population and to the increases in obesity and sedentary behavior [2,3]. The efficacy of THA is well documented, and it is widely accepted that the post-surgery rehabilitation is key to optimize outcomes [4,5], in particular when the rehabilitation is based on intensive and early progressive exercises [6], which lead to improved clinical outcomes and patient satisfaction, and reduction of complications and expenses.…”
Section: Introductionmentioning
confidence: 99%
“…Anterior thigh (quadriceps femoris) and posterior leg (gastrocnemii) muscles were specifically selected for the application of NMES because ICU-acquired muscle weakness and sarcopenia (that could represent a pre-existing condition in COVID patients given their demographic characteristics) have a regional distribution, preferentially affecting lower limb muscles [ 6 , 7 , 34 , 35 ]. The randomized controlled design, blinding of the physician performing the outcome assessments, and use of valid tools for the assessment of physical performance and muscle size (SPPB score and ultrasound-derived muscle thickness, respectively) are notable strengths of the study.…”
Section: Discussionmentioning
confidence: 99%
“…With age, musculoskeletal tissues show increased bone fragility, loss of cartilage resilience, reduced ligament elasticity, and loss of muscular strength, hence increase the susceptibility to develop MSDs (Freemont and Hoyland, 2007; Minetto et al, 2020). Regarding the association between age and the measured serum biomarkers, a previous animal study concluded that aging enhances serum cytokine response in a rat model of work-related MSDs performing a moderate demand repetitive task (Xin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%